African nightshade and African spinach decrease root-knot nematode and potato cyst nematode soil infestation in Kenya - Chitambo, O.; Haukeland, Solveig; Fiaboe, K.K.; Grundler, F.M. (Scientific Societies, 2019)
Plant-parasitic nematodes, particularly root-knot nematodes (RKN: Meloidogyne spp.) and cyst nematodes (CN: Globodera and Heterodera spp.) cause severe yield reduction in most cultivated crops and are of high economic importance. African nightshade (Solanum spp.) and African spinach (Amaranthus spp.) are important African indigenous vegetables (AIV) and are rich sources of nutrition and income. However, their host status to plant-parasitic nematodes remains largely speculative. Therefore, a survey was conducted which revealed that S. villosum exhibited high root galling, whereas on S. scabrum, A. cruentus, and A. dubius root galling was rare or very low. Additionally, soil collected from the rhizosphere of S. villosum and S. scabrum contained few cysts of potato cyst nematodes (PCN), and no developing PCN females were observed on the roots of growing plants. Therefore, we studied the dynamics of RKN and PCN on A. dubius, A. cruentus, S. scabrum, and S. villosum over 2 years in a field experiment. The effects of AIV crop species on RKN and PCN soil infestation were evaluated using susceptible S. lycopersicum or S. tuberosum. After first, second, and third cultivation of A. dubius, A. cruentus, and S. scabrum, RKN infestation of the soil decreased by more than 85%, whereas S. scabrum and S. villosum decreased PCN densities by more than 80%. When cropping susceptible crops, after three seasons of successive cultivation of these AIV, galling index and number of developing PCN females measured on susceptible crops decreased by more than 75%. Wilting and RKN-PCN coinfection incidences also decreased significantly. Here, we present data that support the development of a novel cropping system including African spinach and African nightshade, which reveals a high potential to manage RKN and PCN in an environmentally friendly, effective, and productive way.